Repellency of adults of whitefly Trialeurodes vaporariorum (Heteroptera: Aleyrodidae) with clove and pipper - Aguilar-Astudillo, Eduardo; Rodríguez-Hernández, Cesáreo; Bravo-Mojica, Hiram; Soto-Hernández, Ramón Marcos; Bautista-Martínez, Néstor; Guevara-Hernández, Francisco (Revista Colombiana de Entomología, 2020)
The whitefly Trialeurodes vaporariorum, an economically important pest in vegetables, is managed with synthetic pesticides and has generated resistance with adverse effects on the environment. In the search for alternative management, adult repellence with raw extracts (methanol, ethanol, dichloromethano, and hexane) essential oils, and major compounds of clove and pepper was tested. For this, a treated tomato leaf was placed at concentrations of 1.0 to 0.000001 % within a 1 L beaker containing a 10 mL flask with water. Subsecuently, 20 adults of 2 d of age were introduced. After 3 to 72 h, the posed adults were quantified, and repellence was determined from the difference. The raw extracts, essential oils, and major compounds of clove and pepper repel from 32.5 to 90.2 % of the adult population in 3 to 72 h. The cloves and pepper EO have a better repellent effect than raw extracts and secondary compounds, since they manage to repel 46.2 % to 100 %. The clove EO at the concentration of 1.0 % achieves 100 % repellency at 48 and 72 h after application, while the pepper EO reaches 97.5 % at 72 h after application; in practice, ethanolic crude extract of both plants should be used at a concentration of 0.000001 % since they can repel 38.7 to 87.5 % of adults, from 3 to 72 h, and its repellent effect is maintained; also, it is easier to acquire, safer for the operator, distributor and consumer; and is considered a solvent for the extraction of secondary compounds in organic farming standards.